Deep sequencing of HIV-1 variants from paired plasma and cerebrospinal fluid during primary HIV infection - Arjet Gega; Michael J. Kozal; Jennifer Chiarella; Evelyn Lee; Julia Peterson; Frederick M. Hecht; Teri Liegler; Elizabeth P. St John; Birgitte B. Simen; Richard W. Price; Serena S. Spudich (Elsevier, 2015)
Background: Limited data exist comparing viral quasispecies between cerebrospinal fluid (CSF) and plasma compartments during primary HIV infection. Deep sequencing is a new method to examine the HIV plasma and CSF quasispecies. Methods: In this pilot study, deep sequencing of protease (PR) and reverse transcriptase (RT) was performed in plasma and CSF from participants during primary HIV infection. Estimated mutational load was calculated by mutant variant frequency multiplied by HIV-RNA level. Results: Paired plasma and CSF samples were studied from five antiretroviral therapy-naïve male participants with median 109 days post estimated transmission, age 32 years, CD4 cell count 580 cells/μL, HIV-RNA 5.18 log10 copies/mL in plasma and 3.67 log10 copies/mL in CSF. Plasma samples averaged 7,124 reads of PR and 2,448 reads of RT, whereas CSF samples averaged 7,082 and 2,792 reads, respectively. A distinct drug-resistance pattern with linked mutations present at significant levels (5-10%) was detected in one participant in CSF. Other low abundance variants (>0.2%) were detected in plasma and CSF of four out of five participants. Conclusions: Deep sequencing of CSF HIV is technically possible with sufficient HIV-RNA levels. Differences between the quasispecies in the two compartments detected in one participant, which were present with a high mutational load in CSF at an estimated 3.6 months after HIV infection, suggest that early CNS compartmentalisation may be revealed by sensitive deep-sequencing methods. The presence of distinct low abundance (<1%) resistance variants in plasma and CSF of three other subjects may be significant, but further investigation is needed.